2013
DOI: 10.1007/s10368-013-0232-0
|View full text |Cite
|
Sign up to set email alerts
|

Labour costs dynamics in the Euro area: some empirical evidence

Abstract: Little is known about how the introduction of a common currency and a single monetary policy has affected the labour cost dynamics in the Euro area. The literature has focused mainly on business cycle synchronisation. This paper analyses labour costs convergence in the Euro area since 1995, combining results from different data and two complementary approaches. First we present some relevant facts about wages and unit labour cost dynamics and, in a second phase, we investigate whether the physical introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…2. Geographic Payment Differences: These are differences between purchasing power of two up to n countries, in this research the countries of the European Union (Dao, 2013;Gouveia & Correia, 2013). 3.…”
Section: Included 32mentioning
confidence: 99%
See 1 more Smart Citation
“…2. Geographic Payment Differences: These are differences between purchasing power of two up to n countries, in this research the countries of the European Union (Dao, 2013;Gouveia & Correia, 2013). 3.…”
Section: Included 32mentioning
confidence: 99%
“…RQ1: What are factors for fundamental wages for high skilled employees in IT-departments? (Grund & Westergaard-Nielsen, 2005), (Peng & Eunni, 2011), (Anger, 2007), (Zhao, 2011), (Dao, 2013;Gouveia & Correia, 2013), (Bessette, 2014) RQ2: What are factors for measures to optimize and educate the employee pool with reference to untapped potential within an organization? (Schmidt & Kunzmann, 2006), (Mehairi & Binning, 2014), (LeRouge, Wiley, & Maertz, 2013), (Crow & Liggett, 2014), (Bykov & Shyshkina, 2014), (Asgrahani & Shankararaman, 2014), (Asgarkhani & Shankararaman, 2014), (Grice, Peer, & Morris, 2011) RQ3: What are factors for measures to support the psychological healthiness of the employees?…”
Section: Research Question Publicationmentioning
confidence: 99%
“…This can o¤er guidance to central bankers. For instance, as far as the Euro zone is concerned, it is well known that, in several respects, the members'business cycles have not yet synchronized (Gouveia and Correia, 2013;Caraballo and Efthimiadis, 2012;Koronowski, 2009;Hughes Hallett and Richter, 2008). In these circumstances, our model implies that the ECB executive board should not focus only on Northern countries; it should also carefully consider unemployment developments in Southern ones, as also testi…ed by our empirical results.…”
Section: Discussionmentioning
confidence: 99%
“…6 The slowdown of unit labour costs growth in Portugal was in process before the crisis. For example, Gouveia and Correia (2013), analysing labour costs convergence in the euro area since 1995, concluded that, after the circulation of the euro, Portugal reduced considerably the differential in nominal compensation per employee growth and in nominal unit labour costs growth relative to euro area. levels of inequality in Portugal.…”
Section: Effects On Wages and Inequalitymentioning
confidence: 99%